Inequality in the Economics Profession - Karan Singhal; Eva Sierminska (Global Labor Organization (GLO), 2024)
This chapter presents evidence of the challenges faced by women and underrepresented minorities in Economics. It, first, examines the demographics of the economics profession, highlighting significant disparities in representation. Despite some progress, under representation remains prevalent at different educational levels and at higher academic positions, for the most part. Subsequently, the chapter reviews research on existing barriers and biases contributing to this under representation. Recent work has emphasized the crucial role of attitudes and institutional practices throughout the career pipeline. The chapter highlights evidence of these barriers across different stages of the academic journey, including research endeavors, publication processes, employment opportunities, and promotion and tenure considerations, as well as recent developments related to COVID-19 and the #MeToo movement, which have further influenced discussions on inclusivity and diversity in the field. This chapter underscores the continued need for collective efforts from the economics community to confront these barriers through targeted research and innovative interventions. By enhancing the experiences and opportunities for underrepresented academics, the field of economics could be enriched through fostering a broader range of perspectives, which could also facilitate a deeper understanding of complex societal issues. In line with this objective, the chapter also provides valuable data sources that researchers can utilize to investigate disparities and offer information about collectives and programs dedicated to promoting inclusivity and diversity through mentoring initiatives, research grants, and other forms of support.
Keywords: A11; A20; J15; J16; 330; gender; minorities; economics; tenure; promotion; COVID-19